Manifestações sistêmicas na doença pulmonar obstrutiva crônica - Dourado, Victor Zuniga; Tanni, Suzana Erico [UNESP]; Vale, Simone Alves [UNESP]; Faganello, Márcia Maria [UNESP]; Sanchez, Fernanda Figueirôa [UNESP]; Godoy, Irma [UNESP] (FapUNIFESP (SciELO), 2006)
Chronic obstructive pulmonary disease is progressive and is characterized by abnormal inflammation of the lungs in response to inhalation of noxious particles or toxic gases, especially cigarette smoke. Although this infirmity primarily affects the lungs, diverse extrapulmonary manifestations have been described. The likely mechanisms involved in the local and systemic inflammation seen in this disease include an increase in the number of inflammatory cells (resulting in abnormal production of inflammatory cytokines) and an imbalance between the formation of reactive oxygen species and antioxidant capacity (leading to oxidative stress). Weakened physical condition secondary to airflow limitation can also lead to the development of altered muscle function. Chronic obstructive pulmonary disease presents diverse systemic effects including nutritional depletion and musculoskeletal dysfunction (causing a reduction in exercise tolerance), as well as other effects related to the comorbidities generally observed in these patients. These manifestations have been correlated with survival and overall health status in chronic obstructive pulmonary disease patients. In view of these facts, the aim of this review was to discuss findings in the literature related to the systemic manifestations of chronic obstructive pulmonary disease, emphasizing the role played by systemic inflammation and evaluating various therapeutic strategies.
Systemic manifestations in chronic obstructive pulmonary disease
Keywords: Exercise tolerance; Neuromuscular manifestations; Nutritional status; Pulmonary disease, chronic obstructive/complications; cytokine; chronic obstructive lung disease; exercise tolerance; human; immunology; inflammation; muscle strength; muscle weakness; nutritional disorder; oxidative stress; pathophysiology; physiology; review; skeletal muscle; Cytokines; Exercise Tolerance; Humans; Inflammation; Muscle Strength; Muscle Weakness; Muscle, Skeletal; Nutrition Disorders; Oxidative Stress; Pulmonary Disease, Chronic Obstructive